Institutional Configuration and Competence of the Special Judiciary for Regional Election Disputes: A Comparative Study and Prospects for Implementation - Arifin, Firdaus; Maarif, Ihsanul; Suryana, Cece; Sugiarti, Taty; Murbani, Anastasia Wahyu (Jambura Law Review, 2025)
The dispute resolution system for Regional Head Elections in Indonesia continues to face challenges related to fragmented authority, inconsistencies in judicial decisions, and procedural limitations, which may lead to legal uncertainty and undermine the legitimacy of election outcomes. This study aims to explore the weaknesses of the existing system and propose a more effective institutional model for resolving Pilkada disputes. Employing a normative legal approach with a comparative study method, this research analyzes electoral judicial systems in Mexico, the Philippines, and Germany to identify institutional principles that can be adapted to the Indonesian legal framework. Additionally, this study examines the national legal framework, including Constitutional Court rulings on Pilkada dispute resolution, to assess the effectiveness and limitations of the current mechanisms. The findings indicate that Indonesia’s Pilkada dispute resolution system still suffers from overlapping jurisdiction among institutions, inconsistencies in judicial rulings, and delays in dispute resolution processes. Comparative analysis suggests that a more integrated system, is more effective in ensuring legal certainty and judicial independence. Therefore, this study recommends the establishment of a specialized judicial body for Pilkada disputes, endowed with exclusive jurisdiction, institutional independence, and a transparent and expedited dispute resolution process. The implications of this research highlight that institutional reform in Pilkada dispute resolution is crucial for enhancing public trust in the electoral judicial system, strengthening electoral democracy, and upholding the rule of law in Indonesia’s  Regional Head Elections  process.